Depletion of transglutaminase 2 in neurons alters expression of extracellular matrix and signal transduction genes and compromises cell viability - Yunes-Medina, Laura (Mol Cell Neurosci, 2017)
The protein transglutaminase 2 (TG2) has been implicated as a modulator of neuronal viability. TG2's role in mediating cell survival processes has been suggested to involve its ability to alter transcriptional events. The goal of this study was to examine the role of TG2 in neuronal survival and to begin to delineate the pathways it regulates. We show that depletion of TG2 significantly compromises the viability of neurons in the absence of any stressors. RNA sequencing revealed that depletion of TG2 dysregulated the expression of 86 genes with 59 of these being upregulated. The genes that were upregulated by TG2 knockdown were primarily involved in extracellular matrix function, cell signaling and cytoskeleton integrity pathways. Finally, depletion of TG2 significantly reduced neurite length. These findings suggest for the first time that TG2 plays a crucial role in mediating neuronal survival through its regulation of genes involved in neurite length and maintenance.